EFEKTIVITAS SISTEM MANAJEMEN INFORMASI KEPEGAWAIAN - Seno Andri, Desi Andarwati, Zaili Rusli, (Jurnal Ilmu Administrasi Negara, 2019)
Effectiveness of Staffing Management Information Systems. The purpose of thisstudy was to determine the effectiveness of SIMPEG in Pekanbaru City BKPSDM and find outthe inhibiting factors. This study uses a qualitative descriptive research method approach.Primary data is obtained directly through interviews from key informants, namely the Head ofBKPSDM, Secretary of BKPSDM and BKPSDM Staff. Secondary data obtained from researchdocuments. Data analysis through stages, starting from data collection, data reduction, datapresentation and conclusion drawing. The results showed that the effectiveness of the CivilService Information System (SIMPEG) in the Human Resources Development and HumanResources Agency of the City of Pekanbaru was influenced by input, process and output.Information technology elements cannot be released in relation to the implementation ofSIMPEG. Synergy between technology and its implementation by employees can be seen fromthe implementation of procedures and system workflow processes which include input subsystems,process sub-systems and output sub-systems.